Administration of Public Punishments to Thieves by the Vilnius Castle Court (in the Second Half of the 18th Century) - Stankewicz, Adam; Stankewicz, Adam (Vilnius University Open Series, 2024)
The aim of this article is to discuss the practice of administering public punishments to thieves in the court of Vilnius Castle in the Grand Duchy of Lithuania’s (GDL) central voivodeship in the second half of the 18th century. The aim is to find out to what extent this practice complied with the laws that were in force in the state at that time and to what extent it reflected the humanisation postulates of criminal law that were spreading in the 18th century. The study is based on the court files of the Vilnius Castle Court stored in the Lithuanian State Historical Archives. The Third Statute of Lithuania, approved in 1588, and its provisions regarding the crime of theft still remained in force in the second half of the 18th century. This legal code provided for death, mutilation and flogging for those convicted of theft. In the second half of the 18th century, 36 thieves (all men, one of whom, Kazimieras Jančiauskas, was punished twice) were sentenced to public punishment by the Vilnius Castle Court. The most frequent punishment (49%) was flogging (18 cases), in some cases with the additional punishments of banishment from the city (8 cases) and branding (2 cases). Ten thieves (27%) were sentenced to death, which, as is common in such cases, had to be carried out on the gallows. Nine thieves (24%) were sentenced to fixed-terms (3 to 10 years) or indeterminate (life) prison sentences, to be carried out outside the GDL in Kamjaneć-Podilśkyj. Thus, in cases of theft, the Vilnius Castle Court applied rather severe punishments, basically referring to the relevant norms of the Third Statute of Lithuania, and also, apparently, partly following the tradition of dealing with such cases (in cases where the punishment of flogging was imposed instead of the death penalty). An exception was the use of imprisonment, which was not provided for in the laws of the GDL, but in this case it was only episodic as it was applied in a single sentence in 1782 and originated from the regulation issued by the Permanent Council. Instead of corporal punishments (mostly the death sentence), the philosophers of the Englightenment era proposed the use of imprisonment which would allow to realise the newly defined concept of the repressional punishment – the resocialization of the offender, as well as to implement the principles of proportionality of punishment to the crime committed and the utility of punishment (by using the convicted person for labour). These principles were largely absent from the Vilnius Castle Court’s sentences in the theft cases (except in one case). It is indeed the case that the Court sometimes did make reference to the defendants’ possibility to reform themselves; however, it did not arise from the ideas of Enlightement. The main objectives of punishment still remained the restoration of justice and prevention of crime. As many as 23 out of the 36 convicts (64 per cent) were to be eliminated from society to varying degrees (10 were to lose their lives, 8 were to be banished, 5 were to be sentenced to life imprisonment); therefore it is not possible to talk about resocialisation in this case. The principle of proportionality of punishment was also apparently not implemented when in similar cases the convicted received a different number of lashes. All this can probably be explained by society’s attachment to its own law (in particular to the Third Lithuanian Statute) and to a judicial practice which got established throughout centuries.